Climatic Indices over the Mediterranean Sea: A Review. - Criado-Aldeanueva, Francisco; Soto-Navarro, Francisco Javier (MDPI, 2020)
The Mediterranean Sea, strategically situated across a dynamic frontier line that separates two regions with different climates (Europe and North Africa), has been the focus of attention of many studies dealing with its thermohaline circulation, deep water formation processes or heat and freshwater budgets. Large-scale atmospheric forcing has been found to play an important role in these topics and attention has been renewed in climatic indices that can be used as a proxy for atmospheric variability. Among them, the North Atlantic oscillation, the East Atlantic or the East Atlantic–West Russia patterns have been widely addressed but much less attention has been devoted to a Mediterranean mode, the Mediterranean oscillation. This overview summarizes the recent advances that have been achieved in the understanding of these climatic indices and their influence on the functioning of the Mediterranean from a physical point of view. The important role of the Mediterranean oscillation is emphasized and the most relevant aspects of the other indices are revisited and discussed.
Keywords: Clima mediterráneo; Climatología; Mediterranean Sea; Atmospheric forcing; Climatic indices